Catalase-encapsulated matrix metalloproteinase-9 responsive nanogels for modulation of inflammatory response and treatment of neutrophilic asthma - Xiaoping Guo; Xu Zuo; Wenxue Zheng; Dan Zhao; Chao Dong; Zheng Zou; Yuanyuan Shen; Caina Xu; Chaoliang He; Fang Wang (Journal of Nanobiotechnology)
Abstract Asthma is a chronic disease with typical pathological features such as airflow limitation, airway inflammation and remodeling. Of these, neutrophilic asthma is considered to be the more severe and corticosteroid-resistant subtype of asthma. Increasing evidence suggests that patients with neutrophilic asthma often accompany with dysbiosis of the internal microbiota, where the increased abundance of non-typeable Haemophilus influenzae (NTHi) is closely related to the neutrophilic asthma phenotype. Furthermore, emerging evidence suggests that reactive oxygen species (ROS) are pivotal in the pathogenesis of neutrophilic asthma. In this study, matrix metalloproteinase-9 (MMP-9)-responsive, catalase-loaded nanogels (M-CAT-NGs) were synthesized, which was composed of MMP-9-sensitive peptide (VPMS), arginine-grafted chitosan and maleimide (CS-Arg-Mal), catalase (CAT), sodium citrate (SC) and ε-poly(L-lysine) (ε-PLL). The M-CAT-NGs showed potent antimicrobial effects and exerted excellent therapeutic effects in the presence of MMP-9 by causing VPMS rupture and responsive release of CAT. In vitro experiments revealed that M-CAT-NGs effectively inhibited the proliferation of NTHi, Staphylococcus aureus (S. aureus), and Escherichia coli (E. coli), while also demonstrating the capacity to modulate the inflammatory response induced by lipopolysaccharide (LPS) and hydrogen peroxide (H2O2) stimulation. In vivo experiments demonstrated that nebulized inhalation of M-CAT-NGs was effective in reducing airway hyperresponsiveness (AHR), alleviating inflammation, downregulating the expression level of ROS in the lung tissues, thus enabling the effective management of neutrophilic asthma. Thus, the development of M-CAT-NGs has shown strong potential for the clinical management of neutrophilic asthma by modulating the inflammatory response.